When beauty tamed the beast - James, Eloisa (Avon, 2011)
"Miss Linnet Berry Thrynne is a beauty. Naturally, she's betrothed to a beast. ... Linnet has no idea of the danger posed to her heart by a man who may never love her in return. If she decides to be very wicked indeed, what price will she pay for taming his wild heart?"--Publisher's description.